Spinal inhibitory interneurons: regulators of coordination during locomotor activity - Gosgnach, Simon (Frontiers in Neural Circuits, 2023)
Since the early 1900’s it has been known that a neural network, situated entirely within the spinal cord, is capable of generating the movements required for coordinated locomotion in limbed vertebrates. Due the number of interneurons in the spinal cord, and the extent to which neurons with the same function are intermingled with others that have divergent functions, the components of this neural circuit (now referred to as the locomotor central pattern generator-CPG) have long proven to be difficult to identify. Over the past 20 years a molecular approach has been incorporated to study the locomotor CPG. This approach has resulted in new information regarding the identity of its component interneurons, and their specific role during locomotor activity. In this mini review the role of the inhibitory interneuronal populations that have been shown to be involved in locomotor activity are described, and their specific role in securing left-right, and flexor extensor alternation is outlined. Understanding how these interneuronal populations are activated, modulated, and interact with one another will help us understand how locomotor behavior is produced. In addition, a deeper understanding of the structure and mechanism of function of the locomotor CPG has the potential to assist those developing strategies aimed at enhancing recovery of motor function in spinal cord injured patients.